Room-temperature polariton lasing in all-inorganic perovskite nanoplatelets - Su, Rui (2020)
Polariton lasing is the coherent emission arising from a macroscopic polariton condensate first proposed in 1996. Over the past two decades, polariton lasing has been demonstrated in a few inorganic and organic semiconductors in both low and room temperatures. Polariton lasing in inorganic materials significantly relies on sophisticated epitaxial growth of crystalline gain medium layers sandwiched by two distributed Bragg reflectors in which combating the built-in strain and mismatched thermal properties is nontrivial. On the other hand, organic active media usually suffer from large threshold density and weak nonlinearity due to the Frenkel exciton nature. Further development of polariton lasing toward technologically significant applications demand more accessible materials, ease of device fabrication, and broadly tunable emission at room temperature. Herein, we report the experimental realization of room-temperature polariton lasing based on an epitaxy-free all-inorganic cesium lead chloride perovskite nanoplatelet microcavity. Polariton lasing is unambiguously evidenced by a superlinear power dependence, macroscopic ground-state occupation, blueshift of the ground-state emission, narrowing of the line width and the buildup of long-range spatial coherence. Our work suggests considerable promise of lead halide perovskites toward large-area, low-cost, high-performance room-temperature polariton devices and coherent light sources extending from the ultraviolet to near-infrared range.